(untitled) (Raparin Journal of Humanities (RJH), 2023)
The right of self determination is an internationally endorsed right of nations, especially those nations affected by suppression and assimilation campaigns on their own land. Therefore, nations suffering from economic, political, cultural, and in extreme cases religious and historical marginalization have the right to establish their own independent states. One way to achieve this goal is holding public referendum. Referendums provide the oppressed nations with the opportunity to express their will in a democratic manner and ask for implementation of their inalienable right of self-determination. Since the establishment of the state of Iraq, Iraqi Kurds have been repeatedly oppressed and marginalized by successive Iraqi governments. Brutality of governments in Baghdad pushed Kurds to seek independence to no avail. The region’s geopolitical realities and ongoing conflicts and rivalries over controlling the natural resources of the region have played a major part in Kurdish failure in establishing an independent state. This research explores the diverse aspects of the Kurdish issue in Iraq with the aim of signifying the role geopolitics has played in creation and continuation of problems between the Iraqi government and Kurdistan Region. In order to achieve its stated goal, the research is divided into the following sections: First, an introduction, followed by a section dedicated to emergence and evolution of the Kurdish issue in Iraq. The third section discusses the justifications of Kurdistan’s independence referendum, which is followed by the conclusion section that presents the findings and recommendations of the study.